PF.66 Prognostic Significance an Enlarged Fetal Stomach in the Second Trimester. (26th April 2013) - Richardson, J; Boxall, S; Stanwell, J; Wellesley, D; Brackley, K
Abstract : Introduction: Duodenal atresia classically presents with a "double bubble" sign and polyhydramnios in the third trimester. The significance of an enlarged stomach detected on a second trimester scan is unclear. Methods: A retrospective review of cases identified from the Wessex Fetal Medicine and Antenatally Detected Anomaly (WANDA) regional databases from 1995 to 2012. Scan reports were reviewed and correlated with outcome. Results: 33 cases of an enlarged stomach in the second trimester were identified. In nine there were additional major anomalies: four with gastroschisis, three with cardiac anomalies (including two trisomies), one severe growth restriction with dilated bowel loops and one with renal cystic dysplasia. In the 24 fetuses without additional major anomalies, five had early signs of a "double bubble" with the first part of the duodenum visible. Three (60%) had confirmed duodenal atresia after delivery, one with VATER syndrome and one with trisomy 21. In the 19 cases without an early "double bubble" sign, stomach enlargement resolved in eight (42%) and persisted in 11 (58%), one with polyhydramnios. In these 19 babies there was one neonatal death following preterm labour at 26 weeks post amniocentesis. In the 18 cases with postnatal follow up, there were no gastro-intestinal anomalies or feeding problems detected. Conclusions: The finding of an isolated enlarged stomach in the second trimester appears to have a good outcome with no associated feeding problems. However if an early "double bubble" sign is seen there is a significant risk of an underlying duodenal atresia.